Effects of Incorporation of Black Rice (Oryza sativa L. indica) Extract on Nutritional, Antimicrobial and Antioxidant Properties of Duck Meat Nuggets - Saikia, Kalpita; Laskar, Saurabh Kumar; Das, Ankur; Choudhury, Sadhana; Gogoi, Protiva; Pame, Kuleswan (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during January, 2021–December, 2021 at Dept. of Livestock Products Technology, College of Veterinary Science, Khanapara, Assam, India to evaluate the different quality parameters of duck meat nuggets by adding black rice extract (BRE). Duck meat nuggets were developed using black rice extract as natural antioxidants. This innovative approach not only enhanced the nutritional profile of the nuggets but also contributed to their enhanced flavour, making them a healthy processed food with improved antioxidant properties and shelf life (Gaps required in enhanced the healthy processed food with improved). Four formulations were prepared: Control (0% BRE), Treatment 1 (0.5%), Treatment 2 (0.9%), and Treatment 3 (1.3%). Five batches of duck meat nuggets of each formulation had been evaluated for physicochemical, antioxidant, and microbiological properties. Moisture, crude protein, ether extract, and total ash indicated no significant difference (p<0.05) between control and BRE-treated items. As storage duration increased up to 15 days, the total plate count (TPC) of the control and BRE-treated products considerably increased (p<0.01). However, control products had the highest TPC during storage. Total Viable Psychrophilic Bacterial Count (TVPBC) increased (p<0.01) in all control and BRE-treated items after the 5th day of storage till the 15th day. TVPBC was significantly (p<0.01) lower in the BRE treated samples than in the control sample. Coliform, yeast, mould and Staphylococcus counts were negative for all formulations up to the 15th day. The addition of BRE significantly (p<0.01) increased antioxidant activity in the treated samples compared to the control. Duck meat nuggets with 1.3% BRE (Treatment 3) had the highest antioxidant activity and a 15-day shelf life.